Energy market dynamics as reflected in selected european global indices - Bril, Mykhailo; Petrukhnov, Oleksiy; Mehyar, Samer (My University, 2024)
The energy market plays an important role in providing appropriate resources, both for the needs of each person and for the development of various economic agents. Such provision makes it possible for individual business entities to function normally, to develop the economy and to satisfy the basic needs of people. Energy resources include oil, gas, fuel oil, and coal. The sale of these resources is carried out through their free sale on the market using various instruments in the form of certain securities. For the purposes of energy market analysis, it is important to know the quotes of such securities, taking into account the peculiarities of the functioning of a certain market segment. Based on this, the work examines the dynamics of the energy market as reflected by individual European global indices. The article presents the dynamics of individual indicators of the corresponding indices and conducts their comparative analysis. This allows you to determine the best time to enter the market. The work presents various graphs and diagrams that allow you to understand the progress of the study and evaluate the results obtained.
Keywords: dynamics; stock indices; comparison; analysis; oil; gas; stock market; energy market